ANALISIS FAKTOR MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN MINYAK GORENG PADA PASAR SWALAYAN DI KOTA SURAKARTA - Andryana Damayanti; Suprapti Supardi; Erlyna Wida Riptanti (Universitas Sebelas Maret, 2009)
The aims of this research are to study the factors that is considered by consumers in buying frying oil in swalayan market in Surakarta, and to study the dominant variables which considered by the frying oil consumers swalayan market in Surakarta.